Regional Foresight Community of Practice Training Toolkit: Module 1 – Introduction to foresight - Chesterman, Sabrina; Neely, Constance; Parramon-Gurney, Marie; Fuller, Emma-Jane; Segnon, Alcade C; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This regional foresight training toolkit aims to support a regional foresight community of practice to practically apply the range of foresight tools and methods for innovative strategic planning and policy formulation in their respective institutions. This Module 1 provides an Introduction to applying foresight approaches for climate-resilient agricultural development